Unraveling adaptive evolution: how a single point mutation affects the protein coregulation network. - Knight, C; Zitzmann, N; Prabhakar, S; Antrobus, R; Dwek, R; Hebestreit, H; Rainey, P (Nature Publishing Group, 2012)
Understanding the mechanisms of evolution requires identification of the molecular basis of the multiple (pleiotropic) effects of specific adaptive mutations. We have characterized the pleiotropic effects on protein levels of an adaptive single-base pair substitution in the coding sequence of a signaling pathway gene in the bacterium Pseudomonas fluorescens SBW25. We find 52 proteomic changes, corresponding to 46 identified proteins. None of these proteins is required for the adaptive phenotype. Instead, many are found within specific metabolic pathways associated with fitness-reducing (that is, antagonistic) effects of the mutation. The affected proteins fall within a single coregulatory network. The mutation 'rewires' this network by drawing particular proteins into tighter coregulating relationships. Although these changes are specific to the mutation studied, the quantitatively altered proteins are also affected in a coordinated way in other examples of evolution to the same niche.